2009
DOI: 10.1098/rsbl.2009.0335
|View full text |Cite
|
Sign up to set email alerts
|

Body condition but not dietary restriction prolongs lifespan in a semelparous capital breeder

Abstract: Effects of diet on longevity are complex because acquired resources are shared among growth, reproduction and somatic maintenance. We simplify these axes by examining how dietary restriction and competitive contexts affect longevity using semelparous males of the Australian redback spider (Latrodectus hasselti). Plastic development of L. hasselti males results in trade-offs of body condition against faster development if females are present, facilitating scramble competition. In the absence of females, males d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 29 publications
1
22
1
Order By: Relevance
“…These data support the hypothesis that DR triggers adaptive mechanisms that increase longevity if reproduction can be delayed (Partridge, Gems & Withers 2005). These results are in contrast to a recent study of male redback spiders, in which adult condition and energy expenditure were the strongest predictors of longevity, with no direct effect of DR (Kasumovic, Brooks & Andrade 2009). This sex difference is consistent with life history hypotheses that posit effects of DR depend on how DR shapes the resource allocation trade‐offs inherent to reproduction.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These data support the hypothesis that DR triggers adaptive mechanisms that increase longevity if reproduction can be delayed (Partridge, Gems & Withers 2005). These results are in contrast to a recent study of male redback spiders, in which adult condition and energy expenditure were the strongest predictors of longevity, with no direct effect of DR (Kasumovic, Brooks & Andrade 2009). This sex difference is consistent with life history hypotheses that posit effects of DR depend on how DR shapes the resource allocation trade‐offs inherent to reproduction.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous research has demonstrated that short‐lived male redback spiders survive approximately 20 days after becoming sexually mature (Andrade 2003) and do not increase their longevity under DR (Kasumovic, Brooks & Andrade 2009). It was suggested that this occurs because these males mate only once in their lifetime and die shortly afterwards (Andrade 1996, 2003), so DR should not be associated with reallocation of resources to somatic maintenance (Kasumovic, Brooks & Andrade 2009). This is consistent with the hypothesis that longevity effects of DR depend on allocation priorities shaped by the pattern and frequency of reproduction by adults.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, increased resources have improved the success of both ants (Penick et al 2015) and granivorous birds (Kark et al 2007) in urban areas. In laboratory studies, feeding spiders more food either decreases longevity (Austad 1989;Spencer 1990) or has no effect (Kasumovic et al 2009). However, in the field prey density can increase population density, growth and development of select spider species Miyashita 1986;Wise 1995) but does not always increase spider species diversity (Greenstone 1984).…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, contrary evidence has been reported. For example, DR protocols have failed to increase lifespan in D. melanogaster (Le Bourg and Minois, 1996; Le Bourg and Minois, 2005; Libert et al, 2007; Lee et al, 2008), the nematode C. remanei (Sutphin and Kaeberlein, 2008), medflies (Carey et al, 2002), rotifers (Kirk, 2001; Weithoff, 2007), butterflies (Beck, 2007; Molleman et al, 2009), the spider L. hasselti (Kasumovic et al, 2009), and houseflies (Cooper et al, 2004). Likewise, despite repeated demonstrations that DR can increase the lifespan of laboratory rodents (Weindruch and Walford, 1988; Turturro et al, 1999), recent studies appear to have identified strains that fail to exhibit increased lifespan in response to DR (Harper et al, 2006a; Liao et al, 2010a; Rikke et al, 2010).…”
Section: Introductionmentioning
confidence: 99%